Autoimmune Thrombocytopenia - Ishida, Yoji; Tomiyama, Yoshiaki (Springer Singapore : Imprint: Springer, 2017)
This book provides a concise yet comprehensive summary of the current state of knowledge concerning the pathophysiology, differential diagnosis and treatment options that support day-to-day patient management. It reviews a variety of treatments including TOP-R antagonists, along with Syk inhibitor, which has recently proven to be effective, enabling readers to update and broaden their knowledge of the disease. Covering topics ranging from basic science to clinical practice, Autoimmune Thrombocytopenia will appeal to a wide readership, from medical interns and residents to clinicians and hematologists, offering them a thought-provoking, instructive and informative collection of cutting-edge works. Accordingly, readers will gain an overview of the autoimmune and other causes of the disease, and the book will serve as a foundation for new research directions that further our understanding of the pathophysiology and development of diagnosis and treatment options.